Indikasi Transfer Pricing Pada Perusahaan Sektor Barang Konsumsi di BEI Tahun 2019-2022 - Kamalia, Bellinda Dea; Ratnawati, Juli (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
The purpose of this study is to determine the effect of taxes, tunneling incentive, exchange rates, and bonus mechanisms on transfer pricing. Consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period became the population of this study, selected by purposive sampling techniques. The data analysis used is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and hypothesis test. This study used SPSS 25 with 61 data samples. This research shows that taxes and bonus mechanisms have no influence on transfer pricing. Meanwhile, tunneling incentives and exchange rates have an influence on transfer pricing.